Study of blended surfactants to generate stable foam in presence of crude oil for gas mobility control - Memon, M.K. (Springer Verlag, 2017)
For controlling the viscous fingering in water-alternating gas injection, addition of foam with formation water is more favorable. Use of foam surfactant is one potential solution for reducing gas mobility. The main objective of this research is to generate stable foam for gas mobility control using surfactant blend formulation. Surfactant blends synergistically exhibit better foaming properties than those of individual surfactants. Surfactant blends improve the foam stability and reduces the destabilizing effect of crude oil. Using foam stabilizers may improve foam stability and apparent viscosity; both of these factors are important for improving gas mobility. Alpha olefin Sulfonate (AOSC14-16) was selected as main surfactant, Octylphenol Ethylene Oxide (TX-100) and Lauryl Amido Propyl Amine oxide (LMDO) were selected as additives. Aqueous stability test was performed at 96 °C. Foam stability test was performed in the absence and presence of crude oil. The foam stability and longevity was recorded above the liquid level. Liquid drainage and Foam half-life were noted with respect to time. The mobility reduction factor of three formulations was performed with CO2 by using Berea sandstone cores at 96 °C and 1400 psi. Experimental result showed that surfactant blend of 0.6 AOS + 0.6 LMDO was more stable in presence of crude oil and reduced more gas mobility as compared to an individual surfactant of 0.6 AOS. The maximum generated foam volume and foam half time indicated better performance of the foaming agent. The surfactant blend formulation plays an important role in controlling gas mobility. Strong stability by these formulations indicates that the foam surfactant formulation is of great significance in the field of enhanced oil recovery. © 2016, The Author(s).